2017
DOI: 10.1002/lio2.43
|View full text |Cite
|
Sign up to set email alerts
|

Right dominance in the incidence of external auditory canal squamous cell carcinoma in the Japanese population: Does handedness affect carcinogenesis?

Abstract: Objectives/HypothesisTo investigate the relationship between handedness and the incidence of squamous cell carcinoma in the external auditory canal (EACSCC).Materials and MethodsSixty‐eight cases of EACSCC were enrolled in this study, and their affected side was checked. Handedness and ear‐picking habits were also investigated in 34 EACSCC cases. Handedness was judged based on self‐categorization, and the relationship between handedness and the affected side was investigated.ResultsFifty‐two cases occurred on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…These data all suggest that the mutational patterns of EACSCC mostly resemble those of SCC from other primary sites. Unlike lung SCC or HNSCC, tobacco and alcohol use are unlikely to be major carcinogens of EACSCC; previous clinical studies have reported that chronic inflammation in the external auditory canal induced by habitual ear picking and other mechanical stimuli may cause EACSCC, 37,38 but the exact etiology has remained controversial. In this regard, the mutational pattern of EACSCC in which APOBEC signatures are dominant suggests its link to the mutagenic process associated with chronic tissue damage, as a previous genetic study of aggressive cutaneous SCC demonstrated that chronic inflammation‐induced APOBEC mutagenesis drives carcinogenesis 39 …”
Section: Discussionmentioning
confidence: 99%
“…These data all suggest that the mutational patterns of EACSCC mostly resemble those of SCC from other primary sites. Unlike lung SCC or HNSCC, tobacco and alcohol use are unlikely to be major carcinogens of EACSCC; previous clinical studies have reported that chronic inflammation in the external auditory canal induced by habitual ear picking and other mechanical stimuli may cause EACSCC, 37,38 but the exact etiology has remained controversial. In this regard, the mutational pattern of EACSCC in which APOBEC signatures are dominant suggests its link to the mutagenic process associated with chronic tissue damage, as a previous genetic study of aggressive cutaneous SCC demonstrated that chronic inflammation‐induced APOBEC mutagenesis drives carcinogenesis 39 …”
Section: Discussionmentioning
confidence: 99%
“…Activated EGFR is involved in the pathogenesis and progression of EACSCC the same as HNSCC, 10 but the pathogenesis of EACSCC is not fully understood. EACSCC is often accompanied by a marked inflammatory response and is suggested to be correlated with mechanical stimulations to the EAC 36 . In carcinoma tissues, the close correlation between chronic inflammation and a high risk of carcinogenesis has now been widely confirmed 37 .…”
Section: Discussionmentioning
confidence: 97%
“…In patients with advanced stages of EACC, facial paralysis is also present and is associated with poor survival. Chronic stimulation, such as habitual ear picking, has also been recognized as an important factor in the carcinogenesis of EACC (3).…”
Section: Introductionmentioning
confidence: 99%